EFEKTIVITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) PADA SISWA KELAS VIII DI SMP TERPADU AL-ITTIHADIYAH BOGOR - Fuad Ahmad Riva'i; Idham; Fifih Alfi Wafiroh (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2023)
National Education aims is to form a generation who has good intelligent, faith and noble morals. To realize this national education goal, one of them is through Islamic religious learning. This Islamic Religious Education. aims to educate and direct students become good moslem, tobe obedient servant and have noble character as individuals, family members, communities, citizens of nation and of the world. However, the achievement of the goals of Islamic Religious Education is highly dependent on the effectiveness of the learning carried out by a teacher during the process of teaching and learning activities at school. Therefore this research was carried out with the aim to know out the effectiveness of learning Islamic Religious Education and the factors that influence it occur in eighth grade at the Al-Ittihadiyyah Integrated Junior High School, Bogor. This research is a qualitative research with a case study approach, in which data were collected using structured interviews and passive participatory observation, and collecting relevant documentation as secondary data. Then Data analyzed by techniques the Miles and Huberman model. Based on the results of the study, it can be concluded that the learning effectiveness of Islamic Religious Education in Eighth grade at Al-Ittihadiyyah Integrated Junior High School, Bogor is categorized as good based on achievement of indicators of learning effectiveness such as accuracy in preparing learning programs, use of media and learning resources in the process of teaching and learning activities, establishing good interaction between students and teachers, as well as the implementation of learning evaluations which include the cognitive, affective and psychomotor domains on a regular basis. However, there are a number of things that should be of concern, namely the low level of mastery and cognitive ability. This result can be seen from the average student learning outcomes which are still under the standar minimum. The factors that influence the effectiveness of learning Islamic Religious on studens in this school, such as insufficient of resources and learning media, classes that are not conducive, inadequate internet access, then lack of intelligence and learning motivation student